2018
DOI: 10.1186/s12906-018-2161-5
|View full text |Cite
|
Sign up to set email alerts
|

Zingiber zerumbet L. (Smith) extract alleviates the ethanol-induced brain damage via its antioxidant activity

Abstract: BackgroundZingiber zerumbet (L.) Smith belongs to the Zingiberaceae family that is widely distributed throughout the tropics, particularly in Southeast Asia. It is locally known as ‘Lempoyang’ and traditionally used to treat fever, constipation and to relieve pain. It is also known to possess antioxidant and anti-inflammatory activities. Based on these antioxidant and anti-inflammatory activities, this study was conducted to investigate the effects of ethyl-acetate extract of Z. zerumbet rhizomes against ethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
(36 reference statements)
3
10
0
1
Order By: Relevance
“…Treatment with BCE restored the normal hepatic concentrations of these studied antioxidant enzymes, which suggests the ability of active constituent of the extract to interact directly with ROS and scavenge free radicals [39]. Also, treatment with BCE significantly decreased MDA level by stopping the formation of lipid peroxide from fatty acids [40]. Our results were in line with the previous studies which have shown that the watermelon juice had hepatoprotective effects after excessive ethanol consumption in rats [41].…”
Section: Discussionsupporting
confidence: 90%
“…Treatment with BCE restored the normal hepatic concentrations of these studied antioxidant enzymes, which suggests the ability of active constituent of the extract to interact directly with ROS and scavenge free radicals [39]. Also, treatment with BCE significantly decreased MDA level by stopping the formation of lipid peroxide from fatty acids [40]. Our results were in line with the previous studies which have shown that the watermelon juice had hepatoprotective effects after excessive ethanol consumption in rats [41].…”
Section: Discussionsupporting
confidence: 90%
“…In all, Z. zerumbet proves to have high antioxidant activity through induction of endogenous antioxidant that reduces free radical activity and this can be evidenced by the results of this study. Similarly, this finding is also supported by Hamid et al (2018) that proved the ability of ethyl acetate extract of Z. zerumbet in protecting ethanol-induced brain damages via its antioxidant property.…”
Section: Discussionsupporting
confidence: 64%
“…Regardless of treatment, all animals were killed on Day-20. Prior to killing, the animals were anesthetized with KTX (Ketamine, xylazine and zoletil) with dosage of 0.5 mL/kg (Hamid et al 2018) and decapitated to collect trunk blood and brains for sampling. Blood was collected in plain tubes and allowed to coagulate at room temperature for 3 h. Serum was obtained after centrifugation at 3000 rpm for 10 min and stored at -20°C until further use.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the literature indicates oxidative stress as one of the main mechanisms of CNS damage caused by EtOH [4547], our research is the first to describe the oxidative changes in the cerebellum of rats triggered by the binge pattern and EtOH consumption from adolescence through adulthood in rats. We have shown that even with 4 binge episodes during this period, there is a decrease in total antioxidant capacity (TEAC) and an increase in lipid peroxidation (MDA) levels on the cerebellum; this was previously reported by other studies but through chronic consumption [44, 45, 48]. Even though neural damage mechanisms have not yet been fully understood, oxidative stress is considered one of the most relevant [46, 49].…”
Section: Discussionmentioning
confidence: 81%